Re-Mapping Centre and Periphery Asymmetrical Encounters in European and Global Contexts - Hauswedell, Tessa; Körner, Axel; Tiedau, Ulrich (UCL Press, 2019)
Historians often assume a one-directional transmission of knowledge and ideas, leading to the establishment of spatial hierarchies defined as centres and peripheries. In recent decades, transnational and global history have contributed to a more inclusive understanding of intellectual and cultural exchanges that profoundly challenged the ways in which we draw our mental maps. Covering the early modern and modern periods, Re-Mapping Centre and Periphery investigates the asymmetrical and multi-directional structure of such encounters within Europe as well as in a global context. Exploring subjects from the shores of the Russian Empire to nation-making in Latin America, the international team of contributors demonstrates how, as products of human agency, centre and periphery are conditioned by mutual dependencies; rather than representing absolute categories of analysis, they are subjective constructions determined by a constantly changing discursive context.